2019
DOI: 10.1088/1361-6528/ab40dc
|View full text |Cite
|
Sign up to set email alerts
|

S, N co-doped carbon quantum dots/TiO2 nanocomposite as highly efficient visible light photocatalyst

Abstract: In this paper, we report on the preparation of S, N co-doped carbon quantum dots (CQDs)/TiO 2 nanocomposite using a hydrothermal process where S, N-CQDs were concurrently synthesized and anchored to the surface of the TiO 2 . The prepared nanocomposite was carefully characterized to identify the morphology and structure, crystallinity, chemical composition and optical properties. The photocatalytic activity of the nanocomposite was investigated for degradation of acid red 88 (AR88) under visible light irradiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 78 publications
1
13
0
Order By: Relevance
“…147 Rahbar et al synthesized S,N codoped CQD/TiO 2 nanocomposite for degradation of AR 88 (∼ 77%) under irradiation of visible light. 148 Kim reported the photocatalytic activity of perfluorinated silica-based fluorescent CD/TiO 2 toward MB dye degradation under visible light. 107 Xu et al observed that N-doped CQD loaded on P25 nanoparticles as N-CD/P25 have ∼13 times greater photocatalytic activity for degradation of RhB over P25 (less activity) under visible light irradiation.…”
Section: Photocatalytic Applicationsmentioning
confidence: 99%
“…147 Rahbar et al synthesized S,N codoped CQD/TiO 2 nanocomposite for degradation of AR 88 (∼ 77%) under irradiation of visible light. 148 Kim reported the photocatalytic activity of perfluorinated silica-based fluorescent CD/TiO 2 toward MB dye degradation under visible light. 107 Xu et al observed that N-doped CQD loaded on P25 nanoparticles as N-CD/P25 have ∼13 times greater photocatalytic activity for degradation of RhB over P25 (less activity) under visible light irradiation.…”
Section: Photocatalytic Applicationsmentioning
confidence: 99%
“…The synergistic effect increased the removal rate of bromoethane for 90 min from 54% of pure TiO2 to 94%. Rahbar et al [77] prepared S and N co-doped carbon quantum dots (CQDs)/TiO2 composites using the hydrothermal method. The degradation rate of acidic AR88 The lifetime of photogenerated electron-hole pairs and the region of light response to visible light are vital for TiO 2 to increase the value in pollutant treatment [67].…”
Section: Non-metal Element Doping Modificationmentioning
confidence: 99%
“…The synergistic effect increased the removal rate of bromoethane for 90 min from 54% of pure TiO 2 to 94%. Rahbar et al [77] prepared S and N co-doped carbon quantum dots (CQDs)/TiO 2 composites using the hydrothermal method. The degradation rate of acidic AR88 (azo dyes) under visible light irradiation was 54%, which was higher than that of pure TiO 2 .…”
Section: Non-metal Element Doping Modificationmentioning
confidence: 99%
“…What's more, due to the synergetic effect of multiple heteroatoms doping in the carbon lattice (Wang et al, 2015;Liu et al, 2020;Tripathi et al, 2020), the multielement (like N, Se, B, S, and P) co-doped CQDs have attracted much attention because of their novel properties different from single heteroatom doped CQDs and simple CQDs (Ruiqi et al, 2018;. Co-doped CQDs with different heteroatoms could afford more active sites and improve the fluorescent quantum yield (Ruiqi et al, 2018;Wei J. M. et al, 2018), tuning the photophysical characteristics of CQDs (Zhu et al, 2020), increasing electrical conductivity and specific surface area (Rahbar et al, 2019), obtaining dual-functional mode properties (Mohammed and Omer, 2020), and enhancing the properties of antioxidant capacity, analysis, detection, catalytic, electronic, and optical applications (Samantara et al, 2015;Li et al, 2016;Liu et al, 2019). Among the elements, the doping of nitrogen (N) into CQDs (N-CQDs) could not only improve the quantum yield and fluorescence efficiency but also provide active sites in the CQDs and impart unexpected surface properties to broaden the potential applications in the antioxidation, analysis, catalysis, and so on (Niu et al, 2015;Deng et al, 2018;Lu et al, 2018;Atchudan et al, 2019;Qi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%